Hubungan Pengetahuan dengan Sikap Perawat dalam Memenuhi Kebutuhan Psikologis dan Spiritual Pasien Terminal - Sulaiman Sulaiman; Ismailinar Ismailinar; Anda Syahputra (Malahayati Nursing Journal, 2022)
ABSTRACT Treatment of terminal illness is aimed at masking or hiding the patient's complaints, and providing comfort when the goals of management are impossible to cure. Spiritual needs are basic needs needed by every human being. Spiritual guidance services for patients are increasingly recognized as having an effective role and benefits for healing. The importance of spiritual guidance in health has become a stipulation of the World Health Organization (WHO), which states that the religious aspect (spiritual) is one element of the understanding of complete health. To find out the relationship between knowledge and the attitude of nurses in meeting the psychological and spiritual needs of terminal patients. To analyze the comparison of hemoglobin levels before dan after hemodialysis in patients with chronic kidney failure. The design of this research is descriptive analytic with a cross sectional research design. The population in this study were all nurses in the ICU and ICCU at Langsa City Hospital. The research sample was 45 people using the total population technique. Data analysis technique using chi square test. There is a relationship between knowledge and the attitude of nurses in meeting the psychological and spiritual needs of terminal patients with a value of P (sig) = 0.007. It can be concluded that knowledge can affect nurses' attitudes in providing spiritual care services. The need to improve the attitude of nurses in meeting psychological and spiritual needs in providing care to terminal patients. Keywords: Knowledge, Attitude, Terminal  ABSTRAK Perawatan penyakit terminal ditujukan untuk menutupi atau menyembunyikan keluhan pasien, dan memberikan kenyamanan ketika tujuan penatalaksanaan tidak mungkin disembuhkan. Kebutuhan spiritual merupakan kebutuhan dasar yang dibutuhkan oleh setiap manusia. Layanan bimbingan spiritual bagi pasien semakin diakui memiliki peran dan manfaat yang efektif bagi penyembuhan. Pentingnya bimbingan spiritual dalam kesehatan telah menjadi ketetapan World Health Organization (WHO), yang menyatakan bahwa aspek agama (spiritual) merupakan salah satu unsur dari pengertian kesehatan seutuhnya   Untuk mengetahui hubungan pengetahuan dengan sikap perawat dalam memenuhi kebutuhan psikologis dan spiritual pasien terminal. Desain penelitian ini deskriptif analitik dengan rancangan penelitian cross Sectional. Populasi pada penelitian ini seluruh perawat diruang ICU dan ICCU di RSUD Kota Langsa, Sampel penelitian adalah 45 orang dengan menggunakan tehnik total populasi. Tehnik analisa data menggunakan uji chi square. Ada hubungan pengetahuan dengan sikap perawat dalam memenuhi kebutuhan psikologis dan spiritual pasien teminal dengan nilai P (sig) = 0,007. Dapat disimpulkan pengetahuan dapat mempengaruhi sikap perawat dalam memberikan pelayanan asuhan spiritual. perlunya peningkatan sikap perawat dalam memenuhi kebutuhan psikologis dan spiritual dalam memberikan asuhan kepada pasien terminal. Kata Kunci: Pengetahuan, Sikap, Terminal